LEGAL PROTECTION OF CONSUMERS AGAINST THE CIRCULATION OF ILLEGAL AND DANGEROUS COSMETICS THAT HARM CONSUMERS IN INDONESIA - Alimah, Nur; Mulyani, Asti Sri; Alfiani, Temmy Fitriah (Faculty of Law Universitas Trunojoyo Madura, 2023)
Cosmetics are products that are widely used by the public for personal care and appearancepurposes. However, the circulation of illegal and dangerous cosmetics poses a serious threat to the health and safety of consumers. This research aims to study the challenges faced in protecting consumers from the circulation of illegal and dangerous cosmetics, and analyze how legal protection is provided to consumers regarding the circulation of illegal and dangerous cosmetics that cause harm to consumers. The research method used in this research is normative juridical. This is based on the provisions of Law Number 8 Year 1999 concerning Consumer Protection which regulates the production of cosmetics and also guarantees consumer protection in purchasing cosmetic products. In the event of circulation of illegal cosmetics, warnings, coaching of business actors, and withdrawal of products will be given which will harm consumers themselves. Therefore, increasing supervision of the use and monitoring the circulation of cosmetics without BPOM licenses because this is one of the many illegal cosmetics at this time.